(untitled) (Global Journal of Management and Business Research, 2021)
The paper takes a holistic view of the housing affordability problem to discuss the multifaceted nature of the problem vis-à-vis the political, social, institutional, economic, and financial milieu of Africa. The paper reviews the definitions of housing and housing affordability, and analyses relevant secondary data obtained through archival research and google search to propose practical measures for resolving the problem in the context of the socio-economic, cultural, and political milieu of Africa. It concludes that the enormity of the problem is a function of the vested interest of the power brokers, the market, the unwitting application of western models to Africa, poverty, and the sheer neglect of time-tested African means of affordable housing delivery by the housing policymakers of Africa. A significant fascinating finding is that the people can build cheap houses that no one (including the government, international bodies, aid donors, and especially the market) can do for them. All they need is help with infrastructure provision.